2020
DOI: 10.1016/j.neubiorev.2019.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Why do we move to the beat? A multi-scale approach, from physical principles to brain dynamics

Abstract: Humans' ability to synchronize movement with auditory rhythms relies on motor networks, such as cortical areas, basal ganglia and the cerebellum, which also participate in rhythm perception and movement production. Current research has provided insights into the dependence of this action-perception coupling upon the entrainment of neuronal activity by external rhythms. At a physical level, advances on wearable robotics have enriched our understanding of the dynamical properties of the locomotor system showing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 541 publications
(567 reference statements)
0
76
0
Order By: Relevance
“…Different from the previous researches explored the alterations of FC in FOG+ using the ICA approach, we found that the lessening of FC in the AUN was positively correlated with GFQ and FOGQ scores supported the finding that abnormal connections in the AUN are indeed the cause of FOG. Hearing impairment may be one of the reasons why PD patients often suffer from gait disorders such as falls because perception and action complement each other [ 28 ]. We found increased FC in the PCUN.L and ANG.L of the DMN in FOG+ patients, but Canu et al [ 19 ] found decreased FC in the DMN, which might be the effect of dopaminergic medication because Zhong et al [ 29 ] found that levodopa has the ability to intensify DMN connectivity in PD patients in the ON state.…”
Section: Discussionmentioning
confidence: 99%
“…Different from the previous researches explored the alterations of FC in FOG+ using the ICA approach, we found that the lessening of FC in the AUN was positively correlated with GFQ and FOGQ scores supported the finding that abnormal connections in the AUN are indeed the cause of FOG. Hearing impairment may be one of the reasons why PD patients often suffer from gait disorders such as falls because perception and action complement each other [ 28 ]. We found increased FC in the PCUN.L and ANG.L of the DMN in FOG+ patients, but Canu et al [ 19 ] found decreased FC in the DMN, which might be the effect of dopaminergic medication because Zhong et al [ 29 ] found that levodopa has the ability to intensify DMN connectivity in PD patients in the ON state.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, results showed that subjects automatically aligned to the walking pace only if the rhythm of the vibratory stimulation was close to subjects' preferred walking cadence, while the influence of the vibration was negligible and did not affect the gait when the rhythm was far from the most comfortable one. This is a common behavior, extensively discussed in the literature for different types of cueing [25][26][27][28] and is the reason why we chose the "most comfortable cadence" in Parkinsonian patients. Table 1 summarizes clinical characteristics of patients, including current therapy.…”
Section: Experiments 1: Preparatory Findings In Healthy Subjectsmentioning
confidence: 99%
“…Therefore, WPs are quite accustomed to coordinating their limbs with their own pace, but not with external stimuli such as a rhythmic beat. The introduction of a rhythmic beat induces synchronization of human movements with the beats [ 13 , 15 , 32 , 33 ], and rhythmic body motions are thus modified through the interaction with the external environment, tending towards entrainment [ 34 ]. To prevent this entrainment, one limb must move in an automatic mode by utilizing central pattern generators (CPGs), which are neural circuits producing rhythmic motor movements, such as, walking and swimming, to produce rhythmic movements, whereas the other limb movements are processed through brain activities [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%